Ha-ras in normal and tumoral tissues: structure, function and regulation. (Revista Española de Fisiología, 1996)
The c-Ha-ras1 gene belongs to an eucaryotic ubiquitous gene family which codes important molecules involved in the transduction of mitogenic signals and of cellular differentiation. The c-Ha-ras1 estructure, in four coding exons and a non-coding 5'exon, is highly preserved throughout evolution. This gene, which generates a 1.4 Kb transcript, is expressed in practically all the cell lineages with a tissue-specific pattern. The coded protein, of 189 amino acids and 21 kDa, is a small protein that binds guanine nucleotides (GTP/GDP), is associated with the plasma membrane and possesses low intrinsic GTPase activity. p21ras functions as a molecular switch active when GTP is bound to it and inactive in the GDP-bound form. Its activity is very tightly controlled in the cell by various positive and negative control mechanisms. The ras gene family is the most frequently involved in the development of human and animal tumors. Qualitative (point mutations) and quantitative (over expression) mechanisms of oncogenic activation have been described. The possible relation between determined human Ha-ras1 alleles and the predisposition to cancer has been suggested as well.